Mangrove's species are weak isoprenoid emitters. (5th April 2023) - Fernandez, Catherine; Saunier, Amélie; Wortham, Henri; Ormeño, Elena; Proffit, Magali; Lecareux, Caroline; Greff, Stéphane; Van Tan, Dao; Tuan, Mai Sy; Hoan, Huynh Duc; Bui Nguyen The, Kiet; Dhaou, Dounia; et al.
Abstract: Mangroves are ecosystems interfacing terrestrial and marine environments submitted to extreme abiotic factors (e.g. anoxia, flooding, salinity) producing stress on vegetation. Due to these stresses, we hypothesized that mangroves potentially emit biogenic volatile organic compound (BVOC), particularly isoprenoids as they are defense compounds. Despite mangroves cover only about 5% of the forest areas of the world, their emissions could impact air quality at the continental-ocean interface. As a result, it is important to fill the gap in the knowledge about BVOC emissions from the canopy of the major mangrove trees. The aim of this study was thus to screen isoprenoid emissions of the mangrove species. In this study, we sampled isoprenoid emissions of 14 species foliage among the 38 core species existing in the Indo-West Pacific (IWP) and the Atlantic Est Pacific (AEP) regions. Sampling was performed using a branch-bag dynamic enclosure system and analyzed with gas chromatography coupled to mass spectrometry. Our analysis showed that mangrove tree species are very low emitters suggesting that mangrove ecosystems would not strongly influence atmospheric chemistry and air quality. Graphical abstract: Image 1 Highlights: Isoprenoid emissions of 15 mangrove species were investigated. Mangrove species studied are very low isoprenoid emitters. Mangrove forest weakly contribute to biosphere-atmosphere exchanges through BVOC.